Non-declared consanguinity in Peruvian patients with neurodevelopmental disorder detected trough microarray - Abarca Barriga, Hugo (2023)
Introduction. Consanguinity is the union between people who share a common ancestor, and whose offspring have a higher risk of autosomal recessive diseases, manifesting in some patients as neurodevelopmental disorders. Objectives. To describe non-declared parental consanguinity of patients under 18 years of age with neurodevelopmental disorders, discovered by chromosomal microarray analysis. Methods. Chromosomal microarray analysis was performed on 967 patients with neurodevelopmental disorders between the years 2016-2021 and were selected to patients with regions of homozygosity (ROH) with a value greater than 0.5%. Results. 288 patients were evaluated, 58.3% of the patients were male and 29,8% presented an ROH greater than or equal to 0.5%. We found 25.9% and 0.83% of the patients had their parents of a fifth and first degree of consanguinity not previously declared, respectively. The most frequent neurodevelopmental disorder was delayed psychomotor development with 38.2%. The departments with the highest frequency relative of non-declared consanguinity were Huancavelica, Cajamarca y Apurimac. Conclusions. In Peru, non-declared parental consanguinity is frequent, which is a high-risk factor for the appearance of autosomal recessive diseases in their offspring, how neurodevelopment disorders.